2015
DOI: 10.1007/s11136-015-1035-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining differential responses of youth with and without autism on a measure of everyday activity performance

Abstract: Purpose This study further investigated items with differential item function (DIF) in the Social/Cognitive domain of a measure of everyday activity performance, the Pediatric Evaluation of Disability Inventory-Computer Adapted Test version for Autism “PEDI-CAT (ASD),” to understand possible sources of response variation in a heterogeneous sample of youth with autism compared to the national standardization sample. Methods Cross-sectional design. A convenience sample of parents who identified they had a chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…11 Our research also indicated that performance on items of the Social/Cognitive domain is different for young people with autism and for other populations; 11,12 therefore, the PEDI-CAT (ASD) software incorporates an equating technique to ensure that the criterion-based domain scaled score is a valid measure of a young person's performance, while remaining comparable to scaled scores for this domain obtained in other populations. 11,12 Additional research is needed to establish whether or not the PEDI-CAT (ASD) yields stable scores when change is not expected to occur. Evidence regarding the relationship between PEDI-CAT (ASD) scores and scores from other criterion-standard assessments is also needed to determine how assessment instruments are related to each other and which may be better suited to answering particular research questions.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…11 Our research also indicated that performance on items of the Social/Cognitive domain is different for young people with autism and for other populations; 11,12 therefore, the PEDI-CAT (ASD) software incorporates an equating technique to ensure that the criterion-based domain scaled score is a valid measure of a young person's performance, while remaining comparable to scaled scores for this domain obtained in other populations. 11,12 Additional research is needed to establish whether or not the PEDI-CAT (ASD) yields stable scores when change is not expected to occur. Evidence regarding the relationship between PEDI-CAT (ASD) scores and scores from other criterion-standard assessments is also needed to determine how assessment instruments are related to each other and which may be better suited to answering particular research questions.…”
mentioning
confidence: 72%
“…This study also provided insight into the frame of reference that parents may use when reporting on their child's functional performance. 12 The PEDI-CAT (ASD) software 'speedy' option selects the next item to assess based on the relative difficulty of the previously assessed item and the parent response to that item. However, it appeared that parents often evaluated the appropriateness of each PEDI-CAT (ASD) item based on their child's age, not function.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptations to the PEDI-CAT may also provide an opportunity to address the issue of floor effects evidenced in both the PEDI-CAT and VABS-3 for this population. As the PEDI-CAT publishers have previously made adaptations to items tailored to specific populations, such as ASD [ 25 , 38 ], this could be considered for FXS as well; however, that would require additional validation.…”
Section: Discussionmentioning
confidence: 99%
“…The PEDI-CAT has been translated and cross-culturally adapted into several versions, including Spanish, Dutch and Brazilian-Portuguese [ 19 , 20 ]. It has been used to assess motor functioning in children with learning disorders and children with spina bifida, as well as all domains of functioning in autism spectrum disorder (ASD), Down syndrome, cerebral palsy, Angelman syndrome, infants and toddlers receiving EI services and many others [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Several studies show strong psychometric evidence for the PEDI-CAT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation